2021
DOI: 10.1371/journal.pone.0259388
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postoperative ectopic inner foveal layer on visual function after removal of idiopathic epiretinal membrane

Abstract: Purpose To investigate the functional and anatomical parameters and their postoperative changes according to the ectopic inner foveal layer (EIFL) staging scheme for idiopathic epiretinal membrane (ERM). Methods In this prospective study, patients with idiopathic ERM underwent pars plana vitrectomy and ERM removal, and were followed-up for 6 months. The associations of EIFL with pre- and postoperative functional and anatomical parameters were analyzed. Results A total of 84 eyes (84 patients) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[9,12,21] In addition, when these results were evaluated, as Kim et al also stated earlier, in terms of prognosis prediction, the ERM stage in the new classification made according to the presence of EIFL can be considered to be more useful than EIFL thickness. [13] Since we did not see a significant difference in INL and IPL thicknesses before and after surgery, we thought that the formation of metamorphopsia in this patient group may be due to changes in the outer retinal layers. We observed that preoperative CMT and ONL thickness were positively correlated with preoperative MH and MV scores.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…[9,12,21] In addition, when these results were evaluated, as Kim et al also stated earlier, in terms of prognosis prediction, the ERM stage in the new classification made according to the presence of EIFL can be considered to be more useful than EIFL thickness. [13] Since we did not see a significant difference in INL and IPL thicknesses before and after surgery, we thought that the formation of metamorphopsia in this patient group may be due to changes in the outer retinal layers. We observed that preoperative CMT and ONL thickness were positively correlated with preoperative MH and MV scores.…”
Section: Discussionmentioning
confidence: 60%
“…[19] Kim et al, in their study, in which they included 84 patients with stage 2, 3, and 4 ERM, observed a decrease in visual acuity and an increase in metamorphopsia scores as the ERM stage increased in the preoperative period. [13] They reported that EIFL thickness was correlated with metamorphopsia scores in the preoperative period. Alkabes et al examined 60 eyes with stage 3 and stage 4 ERM and found that metamorphopsia scores were significantly correlated with EIFL thickness and CFT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, an increase in foveal VD and narrowing of the FAZ area are expected mechanical results. 14,15,[17][18][19][20] Our study found a strong positive correlation between CFT and ERM stage in both diabetic and idiopathic ERMs. Additionally, we observed a positive correlation between CFT and foveal VD, while a negative correlation was found between CFT and FAZ area in both types of ERM.…”
Section: Discussionmentioning
confidence: 87%
“…This suggests that the influence of ERM is primarily observed in the inner retinal layers and superficial vascular structures, yet it also highlights its impact on the deeper vascular structures due to ERM traction [12] . In the literature, there are cases in which visual abnormalities may be present without any deterioration in the ellipsoid zone or decrease in visual acuity, and this may be related to the effect of the ERM on the inner retinal layers [13] . In a study conducted with OCT-A, it was shown that there were significant changes especially in the SCP in eyes with ERM; the FAZ area created by SCP was smaller in eyes with ERM than in the macular pseudohole and control groups, and it was suggested that ERM caused a decrease in VD with a direct effect on SCP.…”
Section: Discussionmentioning
confidence: 99%